Kompetensi Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi oleh Guru di SMA - Winanda Amilia; Fitri Maiziani (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
Government Regulation of the Republic of Indonesia Number 74 of 2008 concerning teachers article 3 describes the 4 competencies that a teacher must have. These competencies are pedagogical competence, personality competence, social competence and professional competence. Pedagogic competence and professional competence are closely related to the use of technology in learning. Learning media is a tool or intermediary that functions to facilitate the teaching and learning process so that communication between teachers and students is more effective. This research was conducted to determine the competence of learning media based on Information and Communication Technology by teachers at Senior High Schools in Padang City. The research was conducted in the form of a combination approach that combines quantitative and qualitative methods. these are selected according to the problem under study. The combination of these two approaches will strengthen the study related to the overall phenomenon under study. To obtain quantitative data, a questionnaire was developed based on research indicators.